2009
DOI: 10.1021/es803455d
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Transport of Aquatic Dioxins in the Japanese Watershed: Soil Contamination, Land Use, and Soil Runoff Events

Abstract: Significant dioxins accumulations in Japanese forests and paddy fields have been observed, and surface soil runoff caused by rainfall and irrigation (i.e., soil puddling in paddy fields) results in dioxins input into the aquatic environment. An extensive investigation into the origins and transport of aquatic dioxins in the Yasu watershed, Japan was conducted considering surface soil contamination level, land use, and type of soil runoff event (i.e., irrigation runoff [IR], rainfall runoff [RR], and base flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The present study also showed a strong linear correlation between the dioxin levels obtained via the HRGC/HRMS and DR-CALUX ® . A Chinese study also found a similar correlation between the results of a chemical assay and bioassay (R = 0.87) [8], while several reports found a nonlinear relationship between the results of an in vitro bioassay and the results of the HRGC/HRMS method in dioxin-contaminated soils or sediments [25,27,32,48]. Not all the reports of AhR reporter gene assays including CALUX bioassay found a linear relationship between BEQs and TEQs.…”
Section: Discussionmentioning
confidence: 77%
“…The present study also showed a strong linear correlation between the dioxin levels obtained via the HRGC/HRMS and DR-CALUX ® . A Chinese study also found a similar correlation between the results of a chemical assay and bioassay (R = 0.87) [8], while several reports found a nonlinear relationship between the results of an in vitro bioassay and the results of the HRGC/HRMS method in dioxin-contaminated soils or sediments [25,27,32,48]. Not all the reports of AhR reporter gene assays including CALUX bioassay found a linear relationship between BEQs and TEQs.…”
Section: Discussionmentioning
confidence: 77%
“…Analysis of PCDD/F in the soil is very challenging as concentrations are usually very low and this is exacerbated by run-off of particle-bound PCDD/Fs (Kanematsu et al, 2009a). As such, PCDD/Fs in soil are usually significantly determined in contaminated sites and run-off sites such as paddy fields (Huyen et al, 2015;Kanematsu et al, 2009aKanematsu et al, , 2009b. No PCDD/Fs could be detected above the LOQ at all nine sites, with only three PCDD/Fs being detected from the nine sites sampled.…”
Section: Pcdd/f Trendsmentioning
confidence: 99%